Technology as the God-Command - Ekin Erkan (Labyrinth: An International Journal for Philosophy, Value Theory and Sociocultural Hermeneutics, 2019)
A book Review of Giorgio Agamben's Creation and Anarchy: The Work of Art and the Religion of Capitalism. Stanford, California: 2019.